Influence of Company Size, Leverage, Sales Growth and Operating Capacity on Financial Distress - Wahyu Putra Utama; Erma Setiawati (Journal of Economics, Business, and Government Challenges, 2022)
Financial distress is a condition where the company faces financial difficulties. Financial distress has a close relationship with bankruptcy in a company because financial distress is the stage where the company's financial condition has decreased before the bankruptcy. The purpose of this study was to find out empirical evidence about the effect of firm size, leverage, sales growth and operating capacity on financial distress. The population of this study is Real Estate and Property Companies Listed on the Indonesia Stock Exchange in 2017-2019. The sample in this study is 100 companies that have been selected by the purposive sampling method. The analysis method uses multiple linear regression analysis techniques. The results show that leverage has an effect on Financial Distress while Company Size, Sales Growth and Operating Capacity have no effect on financial distress.